Investigation of the probable anti-cancer effects of the crude methanol extract of dicerocaryum senecioides, (Klotzch) J. Abels, leaves on cervical HeLa cancer cell - Malemela, Kholofelo Mmanoko (My University, 2018)
Dicerocaryum senecioides is a plant widely used as a nutritional source. It is used also for treatment of measles, wounds and to facilitate birth in domestic animal and humans in many parts of southern Africa (Mampuru et al., 2012). Findings in our laboratory have shown that a dichloromethane fraction of D. senecioides possesses antiinflammatory properties in human t-lymphocytes (Madiga, 2009), while the methanol crude extract possesses anti-proliferative and proapoptotic properties against Jurkat T cancer cells (Mphahlele, 2008). In this study, the probable anti-cancer effect of D. senecioides crude methanol leaf extract was investigated on cervical HeLa cancer cells. Dried powdered leaves of D. senecioides were extracted with absolute methanol to obtain a crude extract. To assess the cytotoxicity effect of the extract, KMST-6 and HeLa cell cultures were exposed to various extract concentrations (0 to 600 µg/ml) for 24 and 48 hours and subjected to the MTT assay. The results showed the extract to have no significant increase in the viability inhibition of HeLa cells at all tested concentrations after 24 hours of treatment. However, treatment with 400, 500 and 600 µg/ml of the extract for 48 hours revealed significantly increased HeLa cell viability inhibition. Furthermore, the extract showed to have no effect on the viability of normal human fibroblast KMST-6 cells at concentrations below 600 µg/ml, after 24 and 48 hours of treatment, thus showing selective cytotoxicity of the extract. To determine the mode of cell death associated with the increase in HeLa cell viability inhibition, the Hoechst 33258 nuclear staining assay and inverted light microscopy were employed. The data proposed apoptosis as the mode of cell death associated with the inhibition of HeLa cell viability. This was evidenced by changes in cell morphology such as the loss of HeLa cell radial extensions, cell shrinkage, as well as nuclear morphological features such as chromatin condensation. Apoptosis induction was further confirmed by the annexin-V/PI and multicaspase assays, using flow cytometry. The results showed an increase in the percentage of cells stained with annexin-V/PI, as well as increased caspase activity in extract-treated HeLa cells. To elucidate proapoptotic mechanisms of the extract, Western blotting analysis as well as the human apoptosis antibody array kit were used. This was to measure the expression profile of a number of apoptosis regulatory proteins. The results demonstrated modulation of some anti- and pro-apoptotic proteins, as well as the release of mitochondrial proteins required xiii for initiation of apoptosis, in the cytoplasm. The D. senecioides extract showed to have no effect on the cell division cycle of HeLa cells as determined by the PI staining assay. In conclusion, D. senecioides crude methanol leaf extract induced some degree of apoptosis in cervical HeLa cancer cells via the intrinsic apoptosis pathway. This was by modulating some of the members of the Bcl-2 family of proteins, which, facilitated the release of cytochrome C and activation of a caspase cascade.
Thesis (M.Sc. (Biochemistry) -- University of Limpopo, 2018
Keywords: Dicerocaryum senecioides; HeLa cell radial; Methanol crude extract; Medicinal plants; Cancer cells; HeLa cells